PROGRAM SIMPAN PINJAM KELOMPOK PEREMPUAN (SPP) DALAM MENINGKATKAN KESEJAHTERAAN RUMAH TANGGA MISKIN DI KECAMATAN PANJATAN KAB KULON PROGO (Studi Kelompok SPP di Desa Garongan, Kanoman dan Cerme) - , IKA WIJAYANTI, Drs. Soetomo, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The study about Simpan Pinjam Kelompok Perempuan (SPP, Women Groupâs Saving and Loan) is based on the number of poor population in Panjatan Sub-district. The poverty is mainly because of difficulty in accessing working capital both for starting and developing business. To observe the success of the program in the sub-dictrict in 2009, the study uses Before After analysis that is by comparing the condition before and after receiving the program. Womenâs participation can be seen from their involvement during the programâs phases. Business development and sustainability becomes the parameter of the fund beneficiariesâ improved welfare. The study uses qualitative-descriptive method to explore, understand and explain the emerging phenomenon. The data taken from SPP groups, UPK team and village chief are collected through observation, in-depth interviews and documentation. Panjatan Sub-district is one of the sub-districts in Kulonprogo District which is in general occupied by flat lands at 100 m above the sea level with farming, husbandry, fisheries, plantation, home industry and mining as its potential resources. Based on 2009 data, the sub-district is inhabited by 42,411 population consisting of 20,811 male and 21,677 female population, meanwhile 12,000 of whom are household heads. The finding of the study reveals that the womenâ participation is quite good despite influence by local apparatus. During the phases of the program, the community is given capacity and authority to self-manage the program to allow them to find the best one for themselves. The SPP fund proves to benefit the beneficiaries as it mostly can promote and sustain their business although they no longer borrow SPP fund especially for RTM. Some beneficiaries, in fact, have misused the fund. Instead of using the fund for running their business, they used it for fulfilling their urgent needs. The study also finds out inconsistent distribution of the fund as some has been disbursed to non RTM women. Based on the finding, the researcher suggests that (1) the community, particularly women should be given more intensive dissemination on the urgency of women empowerment through SPP program, (2) it should not take a long time to disburse the fund as the beneficiaries will soon use it for working capital (3) the SPP fund should all be distributed to RTM women (4) periodic assistance should be given to the fund beneficiaries.